2017
DOI: 10.1016/j.cell.2016.12.044
|View full text |Cite
|
Sign up to set email alerts
|

ApoE2, ApoE3, and ApoE4 Differentially Stimulate APP Transcription and Aβ Secretion

Abstract: SUMMARY Human ApoE apolipoprotein is primarily expressed in three isoforms (ApoE2, ApoE3, and ApoE4) that differ only by two residues. ApoE4 constitutes the most important genetic risk factor for Alzheimer’s disease (AD), ApoE3 is neutral, and ApoE2 is protective. How ApoE isoforms influence AD pathogenesis, however, remains unclear. Using ES cell-derived human neurons, we show that ApoE secreted by glia stimulates neuronal Aβ-production with an ApoE4>ApoE3>ApoE2 potency rank order. We demonstrate that ApoE-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
409
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(440 citation statements)
references
References 49 publications
30
409
1
Order By: Relevance
“…A very recent study shows that recombinant and HEK cell-derived apoE can increase A synthesis in human embryonic stem cell-derived neurons in vitro in an isoform-dependent fashion (apoE4 > apoE3 > apoE2) (Fig. 1, dashed red arrow) (42). The observed phenomenon was driven by differences in the isoforms' ability to bind and activate surface apoE receptors, which ultimately activate cFos-containing AP-1 transcription factors and increase APP transcription.…”
Section: Apoe and A Productionmentioning
confidence: 99%
“…A very recent study shows that recombinant and HEK cell-derived apoE can increase A synthesis in human embryonic stem cell-derived neurons in vitro in an isoform-dependent fashion (apoE4 > apoE3 > apoE2) (Fig. 1, dashed red arrow) (42). The observed phenomenon was driven by differences in the isoforms' ability to bind and activate surface apoE receptors, which ultimately activate cFos-containing AP-1 transcription factors and increase APP transcription.…”
Section: Apoe and A Productionmentioning
confidence: 99%
“…However, CX3CL1 deletion increased tau phosphorylation (97), sugCumulative evidence indicates that Aβ and tau aggregates are neurotoxic and trigger neurodegenerative processes in the brain, suggesting that Aβ and tau are central for driving AD pathogenesis (50)(51)(52)(53). Interestingly, APOE4 expression was associated with enhanced Aβ production, driven by increasing APP expression in neurons (54). Additionally, recent GWAS link several immune genes, particularly complement receptor-1 (CR1), CD33, and triggering receptor expressed on myeloid cells-2 (TREM2), with increased AD risk (55).…”
Section: Loss Of Inhibitory Signalsmentioning
confidence: 99%
“…It has also been reported that apoE may compete with Ab for interaction with LRP1 (12) and that apoE directly regulates neuronal Ab production in an isoform-dependent manner (13). A complete understanding of the mechanisms by which apoE regulates AD risk therefore remains an unresolved question.…”
Section: Introductionmentioning
confidence: 99%